The Devil: a very short introduction - Oldridge, Darren (Very short introductions, 2012)
"The Devil has fascinated Christians since the time of the New Testament, and inspired many haunting works of art. This Very Short Introduction looks at the Devil in the history of ideas and in the lives of real people. Darren Oldridge shows us that the Devil is an important figure in western history--a richly complex and contradictory one. Oldridge focuses on three main themes: the idea of the Devil being integral to western thought from the early Middle Ages to the beginnings of modernity; the belief that the Devil represents the mirror image of goodness; and the multiplicity and instability of ideas about the Devil. Oldridge concludes by exploring "demonological" ways of thinking in our own time, including allegations of "satanic ritual abuse.""--